Factors affecting supragingival biofilm composition. II. Tooth position - Haffajee, A. D. (2008)
OBJECTIVE: To test the hypothesis that tooth location affected the microbial composition of supragingival plaque beyond the effect due to plaque mass as reflected by total DNA probe count. METHODS: Supragingival plaque samples were taken from the mesiobuccal aspect of each tooth in 187 subjects at baseline (N samples = 4,745). All samples were individually analyzed for their content of 40 bacterial species using checkerboard DNA-DNA hybridization. Significance of differences in mean species counts and proportions were determined among tooth surfaces and 6 tooth type categories: molars, bicuspids, incisors/canines in the mandible and maxilla separately using the Kruskal Wallis test. Stepwise multiple linear regression was employed to examine the relationship between species proportions and total DNA probe count, tooth location, periodontal and smoking status, age and gender. RESULTS: All species differed significantly among tooth types and among the 6 tooth categories. Higher plaque levels were seen at molars and lower incisors. Some differences observed between tooth types could be partially explained by the level of plaque. Teeth with high plaque mass exhibited high levels of Capnocytophaga gingivalis, Actinomyces naeslundii genospecies 2, Campylobacter rectus and Campylobacter showae. However, certain species such as Veillonella parvula and Streptococcus sanguinis differed significantly at different tooth locations despite similarities in plaque mass. Twenty of the test species exhibited a significant association with tooth location after adjusting for total DNA probe count and subject level factors. CONCLUSION: While plaque mass was associated with differences in proportions of many species in supragingival biofilms, tooth location also was strongly associated with species proportions in both univariate and multivariate analyses.